Fear of COVID-19 pandemic (coronaphobia) amongst young adults in India - Verma, Aditi; Biradar, Ashwini (International Journal Of Community Medicine And Public Health, 2021)
Background: The Novel Coronavirus disease has inherently brought a fear of uncertainty and continuity resulting in broad psychological effects on the mental health of the present generation. Although, few studies have tried to evaluate the degree of fear of COVID-19 but none has been done on young adults especially dental undergraduate healthcare providers so far. Hence, the present study aims to assess the fear of COVID-19 among young adults in India. Methods: A web based study was conducted on a sample of 309 dental undergraduate students of age group 18-25 years (young adults). The participants were asked for responding to a standardized online questionnaire prepared on google form that included the recently developed 7-item Fear of COVID-19 Scale (FCV-19S) to assess emotional fear reactions. Results: Overall mean fear score for the study population was 18.09+6.79. A significantly higher number of the study population reported low fear (56.6%). Age, place of residence, academic year, steady source of income and the students whose relative/friend got covid-19 depicted a significant difference based on the level of fear (p<0.05). Females and the students staying alone displayed higher levels of fear compared to their respective counterparts. Conclusions: Fear is a common psychological outcome during pandemics especially amongst healthcare providers as COVID-19 pandemic is a continuously evolving disease outbreak related to stress, disease contraction and dying. Thus, managing this fear in the young minds is imperative in order to reduce the psychological implications affecting their mental health due to the current COVID crisis.